1983
DOI: 10.1002/ar.1092060212
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method for quantitative stress analysis in bones by three‐dimensional photoelasticity

Abstract: Comparative critical examination of methods suitable for studying stress in bones have shown that the three-dimensional photoelastic method is one of the most reliable. Described herein is the method for obtaining, by fusion, full-scale models in epoxy resin, that are exactly equivalent to external shape of the prototypes.This technique offers the advantages of being applicable without variation to any bone segment and of enabling a large number of additional resin castings to be made from the same mould. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The finite element method predicts that, in the case of long bones, the direction of principal strain will be similar on the bone surface and deep to the surface. This finding also gains support from data obtained using the photoelastic method2 of stress analysis (see Bianchi et al, 1983) 'Certain plastic materials become birefringent when loaded and observed in polarized light. By constructing and loading a plastic model of a bone, it is possible to see lines (or fringes) of differing optical intensity which reveal the trajectories of stress that occurred in the element during loading.…”
Section: Discussion Assumptionssupporting
confidence: 52%
“…The finite element method predicts that, in the case of long bones, the direction of principal strain will be similar on the bone surface and deep to the surface. This finding also gains support from data obtained using the photoelastic method2 of stress analysis (see Bianchi et al, 1983) 'Certain plastic materials become birefringent when loaded and observed in polarized light. By constructing and loading a plastic model of a bone, it is possible to see lines (or fringes) of differing optical intensity which reveal the trajectories of stress that occurred in the element during loading.…”
Section: Discussion Assumptionssupporting
confidence: 52%
“…For the femur model construction the technique develbped in the previous study (Bianchi et al, 1983) was :mployed. A full-size model of a normal human femur was obained by placing the bone in a suitable aluminum conainer int0 which was poured an elastomer formed from wo liquid components (RTV-M 533 with T 35 Wacker iardener), which, when mixed in appropriate proporions, solidify.…”
Section: Methodsmentioning
confidence: 99%